"Big Sister" Wisdom: How might non-Indigenous speech-language pathologists genuinely, and effectively, engage with Indigenous Australia?. (4th May 2019) - McDermott, Dennis
Abstract: Speech Pathology Australia, through its landmark project for the profession, "Speech Pathology 2030 - making futures happen" (SP 2030), calls for speech-language pathologists to "respond (to presenting clients) in ways that respect each person's culture, language, life experiences, and preferences" (Speech Pathology Australia, 2016, p. viii). Such engagement, it holds, is central to successful practice. Meeting the needs of Aboriginal and/or Torres Strait Islander (Indigenous) clients and communities, however, requires a skilled response to client wholeness, to their indissoluble, and unique, immersion in their: indigeneity; lived cultural experience; and the social, geographical, economic and political realities that surround them. Equally, the achievement of a truly-effective engagement, one able to engender desired outcomes, is also dependent on the challenging achievement of culturally-safe practice. Given that the relevant literature is, historically, based on a privileging of western purviews, this article asserts the validity of incorporating (pan-)Indigenous epistemologies and perspectives. As well as the Indigenous health and cultural safety literature, then, this article draws on particular Indigenous professional experience as a locus of good-practice evidence, one capable of contributing additional insights to best address the question: "How might Non-Indigenous speech-language pathologists really engage, effectively, with Indigenous Australia?". It introduces a guiding rubric, "Meet People in their Own Reality", as a tool with which to examine how engagement, in the service of more-effective practice, can be optimised in four exemplar domains of SP 2030.